2022
DOI: 10.1155/2022/8752375
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Surgical Strategy and Prognosis of Pancreatic Neuroendocrine Tumors Based on Smart Medical Imaging

Abstract: It is imperative to seize the “golden rescue time” and implement new concepts and new skills in modern trauma rescue. Combining with the development background of smart medical image analysis, this topic focuses on surgical strategies and prognostic measures and studies a serious and difficult disease frequently occurring in middle-aged and elderly people: pancreatic neuroendocrine tumors. This article uses the comparative test method and sample collection method to collect the medical records of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…IPAS is innocuous in nature and generally does not require any treatment. However, surgery and/or chemotherapy are recommended for PNETs[ 10 ]. Unfortunately, the overlap of imaging features between IPAS and small (< 3 cm) hypervascular PNETs often requires surgical management[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…IPAS is innocuous in nature and generally does not require any treatment. However, surgery and/or chemotherapy are recommended for PNETs[ 10 ]. Unfortunately, the overlap of imaging features between IPAS and small (< 3 cm) hypervascular PNETs often requires surgical management[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%